Agricultural Development and Calorie Consumption in Rajasthan: An Analysis through Econometric Modelling - Dixit, A K; Agarwal, S K; Singh, Padam (Annals of Arid Zone, 2016)
The agricultural development is linked with calorie-consumption as it makes available the subsistence production and generates income to buy sufficient food. The calorie consumption, was studied in two districts, Jodhpur (with inadequate agricultural development) and Jaipur (with adequate agricultural development). Using econometric models it is found that marginal propensity to obtain a calorie intake in relation to household income is only 0.083 in case of Jodhpur and tends 'to be negative in case of Jaipur with agricultural development. However, raising subsistence production by one unit, the calorie intake is almost doubled in Jodhpur. The local food preferences are of paramount importance here. The results suggest that in order to check calorie-inadequacy in desert population through agricultural development, the strategies should be to promote more the subsistence production of local calorie-rich ' crops.